Opinion 2475: Tibicina Kolenati, 1857 and Lyristes Horvath, 1926 (Insecta, Hemiptera): usage conserved by the suppression of Tibicen Berthold, 1827; Cicada Linnaeus, 1758 (Insecta, Hemiptera): usage conserved by designation of Cicada orni Linnaeus, 1758 as the type species - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved current usage of the generic names Tibicina Kolenati, 1857 and Lyristes Horvath, 1926 by suppressing the generic name Tibicen Berthold, 1827 for the purposes of the Principle of Priority but not for those of the Principle of Homonymy. The International Commission on Zoological Nomenclature has also conserved current usage of the generic name Cicada Linnaeus, 1758 by designating Cicada orni Linnaeus, 1758 as the type species.
Keywords: Nomenclature; taxonomy; Hemiptera; CICADIDAE; Tibicininae; Lyristinae; Cicada; Tibicen; Tibicina; Cicada orni; Holarctic